Autoritarismo y violencia : la perspectiva del conservadurismo hispanófilo : el caso de Rodulfo Brito Foucher (1938) - Urías Horcasitas, Beatriz (El Colegio de México, 2014)
This article examines Rodulfo Brito Foucher’s views on autoritharianism and violence. Brito Foucher was an important political opponent under Cárdenas’ rule. He also was a conservative ideologist who envisioned a “necessary dictature” as an alternative that would put an end to Mexico’s decline and corruption. In the essays he published in 1938, Brito Foucher relates specific political events —linked to Tomás Garrido Canabal’s regime in Tabasco between 1924 and 1935— to the rejection of the revolution that put in place a dictatorship disguised into a democratic regime. Reviewing Brito Foucher’s arguments allows one to reexamine from a new perspective the meaning of two key-concepts within the history of Mexico’s social thinking in the 20th century.